PENYEBARAN SPOILER DI MEDIA TIKTOK TERHADAP FILM SPIDERMAN: NO WAY HOME PERSPEKTIF HUKUM PIDANA ISLAM - Puji Setyaningtias; Atika Atika (Tazir, 2023)
Spiderman: No Way Home will be released on December 15, 2021. Spoilers for this film are circulating on the internet, especially on the Tiktok application which is currently being used. The problem with this spoiler, the author found accounts that spread spoilers for the Spiderman: No Way Home movie by uploading snippets of the film on Tiktok media. This is where the formulation of the problem emerges as follows: 1) How is the crime of spreading spoilers on Tiktok media in the case of the Spiderman: No Way Home film? 2) How does Islamic criminal law review the spread of spoilers on Tiktok in the case of the Spiderman: No Way Home film? This research is a normative juridical research. The research method in this study is through a library research approach, with the data used are secondary data, and the sources of data taken in this study are primary, secondary and tertiary legal materials. The data collection is carried out by literature study of legal materials obtained from data that has been processed and obtained from research results, then collected, read, recorded and described by inductive thinking, namely from general to specific questions so that the results are presented. research results can be easily understood. Based on the results of this thesis research, it can be concluded that: 1) The crime of spreading spoilers in the Tiktok media against the Spiderman no way home case is a cyber crime in the form of offense against intellectual property, namely a crime against intellectual property rights. Spoiler actions violate article 32 of the ITE Law, because spoilers are categorized as "transmission" actions and the sanctions are a maximum imprisonment of eight years and/or a fine of two billion, as regulated in article 47 of the ITE Law. 2) A review of Islamic criminal law on the spread of spoilers on Tiktok media in the case of the film Spiderman: No Way Home, namely that spoilers are the act of taking other people's work without permission or plagiarism. Plagiarism can be categorized as an act of theft. So in Islamic crime the sanction for the perpetrator is cutting off his hand as in the letter Al-Maidah verse 38. However, the theft in the form of spoilers does not meet the conditions for the hadd punishment, thus requiring the ta'zir punishment. Keywords: Spread, Spoiler, Tiktok